Country of origin dan keputusan pembelian konsumen otomotif: Peran nilai terpersepsi sebagai pemediasi - Niko Handoyo; Albert Kriestian Novi Adhi Nugraha (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
The current research aims to test the influence of country of origin on car purchase decision through an intervening variable, perceived value. New product faces the big challenge to generate positive consumer responsess as it comes from a country associated with past negative stereotype. This research tests a structural model for validating whether country of origin is a relevant variable in consumer purchase decision of high involvement product such as automotive product. A proposed structural model comprises an exogenous variable (country of origin), an intervening variable (perceived value), and endogenous variable (consumer purchase decision). This research applies non-probability sampling method and purposive sampling technique to collect ninety respondents which were the owner of Wuling car. They filled-out the structured- questionnaires. The data was analyzed by using the structural equation modeling partial least squares (SEM-PLS) which consised of two stages: measurement model and structural model evaluations. The result indicates that perceived value partially mediates the relationship between country of origin and consumer puchase decision.